BERPIKIR RASIONAL-ILMIAH DAN PENDEKATAN INTERDISIPLINER DAN MULTIDISIPLINER DALAM STUDI HUKUM KELUARGA ISLAM - Nasution, Khoiruddin (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
This short article tries to explain how important it is to think rationally and scientifically, place the position of approachment in the Study of Islamic Family Law, also describe the use of Interdisciplinary and multidisciplinary approach to understand and practice the Islamic Family Law. In conclusion, there are three conclutions. First, students need to get used to think, write, speak and act rationallly and scientifically. The process can be carried out by integrating with the entire subjecy. Second, needs a good and comprehensive understanding of approachment positions in the study of Islamic Family Law, both in relation to habituation of thinking, writing, speaking and acting rational and scientific as well as in effort to integrate and interconnect Islam and science. Third, it is necessary to habituate using an interdisciplinary and multidisciplinary approach to understand and observe all matters that related to the Islamic Family Law. [Tulisan singkat ini mencoba menjelaskan bagaimana pentingnya berpikir rasional dan ilmiah, meletakkan dimana posisi pendekatan dalam Studi Hukum Keluarga Islam, sekaligus menggambarkan penggunaan Pendekatan Interdisipliner dan Multidisipliner dalam memahami dan mengamalkan Hukum Keluarga Islam. Kesimpulannya ada tiga. Pertama, mahasiswa perlu dibiasakan berpikir, menulis, berbicara dan bentindak rasional dan ilmiah. Proses pembiasaannya dapat dilakukan secara terintegrasi dengan seluruh mata kuliah. Kedua, perlu pemahaman yang baik dan konprehensif bagaimana posisi pendekatan dalam studi Hukum Keluarga Islam, baik dalam kaitannya dengan pembiasaan berpikir, menulis, berbicara dan bentindak rasional dan ilmiah maupun dalam upaya integrasi dan/atau interkoneksi keilmuan. Ketiga, perlu pembiasaan menggunakan pendekatan interdisipliner dan multidisipliner dalam memahami dan mengamalkan segala persoalan yang berkaitan dengan Hukum Keluarga Islam.]